Impacts of components of glaciosphere to climate change at the Antarctic Penisnula region - V. F. Grischenko; V.E. Timofeyev; S. V. Klock (Ukrainian Antarctic Journal, 2005)
Behaviour of the most important components of glaciosphere as glaciation and sea-ice in the region of the Antarctic Peninsula in conditions of climate warming is considered. Glaciological study is based on the mass balance measurements commenced by the British in 1960s and continued by Ukrainians scientists on small ice-cap of Galindez Island. General evolution of the glacier state is well-agreed with the decadal changes of the mean air temperatures: accumulation dominated in 1950s and early 60s in conditions of slight cooling; nearly-equilibrium state with first signs of ablation were observed in 1970s, when first indicators of climate warming appeared; then ablation covered 1980s, with further acceleration in 1990s. General trend to the glacier’s recession is clearly expressed at present, with the formation of new crevasses and calving of its marginal parts. This coincided with the recent collapse of the Northern part of the Larsen Ice shelf during the recent years and other signs of glaciers' recession at Antarctic Peninsula.The contribution of the tropospheric circulation to the mass-balance on glaciers is shown, as well as its importance to the formation of ocean currents and sea-ice transport through Bransfield Strait across the coastal zone of Graham Land. The most intensive westward ocean current with sea-ice transport through Bransfield Strait is formed at the southern flank of cyclones migrating through the Drake Passage.Variability in sea-ice by the data of remote microwave sounder as well as data of local observations showed general growth of its amount and extension during the summer seasons for the last two decades, at the vicinity of Vernadsky base as well as at western coast of Graham Land and Northern Weddell Sea. This tendency of the Antarctic sea-ice to expansion during summer months is in contrast with that in Northern Seas: sea ice in Arctic is significantly reduced on the background of warming. In winter, sea ice remains at some multi-years’ average limits, although timing of fast ice preservation is significantly shortened and the amount of icebergs increased in comparison with colder winters in 1950s and 1960s.Commencement of research into glaciation at the Antarctic Peninsula region in the frames of International Polar Year, 2007-09 is expected to be a new important stage in studying its mass-balance, dynamics and regime in conditions of climate change.